Science Teacher Identity in Environmental Chemistry Education Using the STEM Approach: A Bibliometric Analysis of Scopus Journals (2015–2024) - Widyaningsih, Mia; Hernani, Hernani; Mudzakir, Ahmad; Supriatna, Asep; Kamaludin, Agus; Ragadhita, Risti (Journal of Educational Sciences, 2025)
This study aims to investigate how Environmental Chemistry education contributes to shaping the science teacher identity of prospective chemistry teachers through a STEM approach. The bibliometric analysis method was conducted using Scopus data (2015–2024), analyzed with Biblioshiny and VOS Viewer. From an initial 483 documents, 418 relevant works comprising articles, books, and reviews were selected based on keywords such as "Science Identity", "Science Teacher Identity", "STEM Education Approach", and "Environmental Science Chemistry". Biblioshiny was used to identify trends over the decade, including annual publication rates, key journals, influential authors, productive affiliations and countries, globally cited articles, and frequently occurring keywords. VOS Viewer further enhanced the analysis by offering three types of visualizations network, overlay, and density to illustrate the relationships and research trends among the selected publications. These visual tools reveal the interconnectedness of topics and highlight emerging areas in the field. The findings offer valuable insights into the global development of research at the intersection of science identity, STEM education, and environmental chemistry. This bibliometric exploration provides a foundation for researchers to identify current trends, understand the research landscape, and recognize gaps that can inform future studies.